Pedagogical and Epistemic Knowledge in Special Education and its Migratory Challenge Towards Inclusive Education - Vásquez-Burgos, Karina R. (2020)
The purpose of this article of reflection is to share ideas of the comprehensive framework in the pedagogical and epistemic knowledge of Special Education. What it allows, to address the constructions facing the paradigmatic shift of migration towards an Inclusive Education that from the XX century takes a leading character in the pedagogical knowledge of Latin American education. Among the discourses that Inclusive Education involves, there is equality of opportunities, with evident epistemological gaps within pedagogical knowledge, generating hybrid and incoherent subtleties referring to the challenges and dilemmas that the inclusion of students in traditional educational systems tends to. These paradigmatic and epistemological dilemmas that surround this migration of a traditional knowledge in Special Education, is the reason for critical analysis, which is bearable to problematize the inconsistencies that are being generated as a result of the re-signification of a pedagogy, that from its Early considered an education under normalization processes, with exclusionary and even tendencies and that currently presents transforming ideas, on an approach in evolution that seeks an episteme based on Inclusive Education.